Complementary feeding intervention on stunted Guatemalan children: a randomised controlled trial - Boris Martinez; Meghan Farley Webb; Ana Gonzalez; Kate Douglas; Maria del Pilar Grazioso; Peter Rohloff (BMJ Publishing Group, 2018)
Objective/background Guatemala's indigenous Maya population has one of the highest rates of childhood stunting in the world. The goal of this study was to examine the impact of an intensive, individualised approach to complementary feeding education for caregivers on feeding practices and growth over usual care.Design An individually randomised (1:1 allocation ratio), parallel-group superiority trial, with blinding of study staff collecting outcome data.Setting Rural Maya communities in Guatemala.Participants 324 children aged 6-24 months with a height-for-age Z score of less than or equal to −2.5 SD were randomised, 161 to the intervention and 163 to usual care.Interventions Community health workers conducted home visits for 6 months, providing usual care or usual care plus individualised caregiver education.Main outcomes measures The main outcome was change in length/height-for-age Z score. Secondary outcomes were changes in complementary feeding indicators.Results Data were analysed for 296 subjects (intervention 145, usual care 151). There was a non-significant trend to improved growth in the intervention arm (length/height-for-age Z score change difference 0.07(95% CI −0.04 to 0.18)). The intervention led to a 22% improvement in minimum dietary diversity (RR 1.22, 95% CI 1.11 to 1.35) and a 23% improvement in minimal acceptable diet (RR 1.23, 95% CI 1.08 to 1.40) over usual care.Conclusions Complementary feeding outcomes improved in the intervention arm, and a non-significant trend towards improved linear growth was observed. Community health workers in a low-resource rural environment can implement individualised caregiver complementary feeding education with significant improvements in child dietary quality over standard approaches.Clinical trial registration number NCT02509936.Stage: Results